(untitled) - Leitman, Seth (New York, 2013)
Thoroughly revised and expanded, Build Your Own Electric Vehicle, Third Edition, is your go-to guide for converting an internal combustion engine vehicle to electric or building an EV from the ground up. You'll also find out about the wide variety of EVs available for purchase and how they're being built. This new edition details all the latest breakthroughs, including AC propulsion and regenerative braking systems, intelligent controllers, batteries, and charging technologies.
Keywords: Automobiles, Home-built,Xe điện,Xe hơi tự động, xây dựng nội địa, Electric vehicles; Thiết kế và xây dựng,Design and construction